Humanitarian Philanthropy amid Genocide in Gaza: An Observational Humanitarian Field Study - Basuki Supartono (Bulan Sabit Merah Indonesia, 2026)
The genocide in Gaza has caused widespread destruction of communities, healthcare systems, and the environment. However, direct field evidence on humanitarian healthcare disruption remains limited. This observational humanitarian study aimed to document and analyse the humanitarian catastrophe in Gaza. Direct field observations in Southern Gaza assessed healthcare disruption, humanitarian conditions, and environmental degradation during an 11-day deployment in April–May 2025. Humanitarian access remained restricted throughout the mission. Destruction of healthcare and public infrastructure disrupted health services, humanitarian operations, and civilian mobility. Environmental degradation was evident across affected areas. Shortages of medicines, medical supplies, food, clean water, electricity, and fuel severely constrained care. Many displaced civilians lived in temporary shelters and overcrowded settings. Personnel at Nasser Medical Complex worked prolonged hours despite severe resource limitations. The Indonesian EMT treated approximately 100 patients and initiated voluntary blood donation activities. Under Rahma Worldwide Mission 32, the Indonesian and Qatari teams managed 434 consultations and emergency cases, performed 169 surgical procedures without intraoperative mortality, assisted eight normal deliveries, and treated 53 patients with non-communicable diseases. The Indonesian EMT also provided humanitarian medical education, capacity building, and clinical training in regenerative medicine and wound management, and established a pain clinic for patients. These findings underscore the multidimensional impacts of genocide on civilian survival, healthcare systems, and social resilience in Gaza. The Indonesian EMT experience highlights the urgent need to end the genocide, protect civilians, sustain medical support, and support long-term recovery.